Pengembangan Perangkat Pembelajaran IPA Terpadu Lintas Materi pada Mata Pelajaran Biologi dengan Tema Sampah - Jena Andres; Sumira Gailea (Peneliti.net, 2021)
Preliminary research conducted by the author on the implementation of science learning at SMP N 1 Tidore Islands showed that science learning had not been given in an integrated manner. Science Basic Competencies (KD) have not been integrated so that there are no integrated science teaching materials that can be used during the learning process. The making of teaching materials begins with the integration of Basic Competencies from several science studies. The learning assessment process can be carried out through the development of teaching materials which aims to develop the teaching profession and overcome student failures in learning. This study aims to develop integrated science teaching materials through the development of tools on environmental pollution material with the theme of waste and to determine the achievement of student learning outcomes in accordance with the Minimum Completeness Criteria (KKM). The research method used is Research and Development to produce integrated science teaching materials and test their effectiveness. In the early stages of research, the teaching materials used for research are validated by the teaching materials validators. The next process is the application of teaching materials in the learning process. The results showed that the integrated science teaching materials were very feasible to be used in the learning process. The use of integrated science teaching materials has an effect on student scores so that 86% of students' scores reach the minimum completeness criteria. The conclusion of this study is that integrated science teaching materials are included in the very good category to be used as a learning resource for students of SMP N 1 Tidore Islands, so that students are able to achieve learning outcomes that are in accordance with the Minimum Completeness Criteria.